Impacts of Regulatory Transformation Processes to the Downstream Oil Market in Turkey - Metin, Erol Seyfi; Kumbaroglu, Gurkan (International Journal of Energy Economics and Policy, 2018)
This paper is a review of the regulatory transformation process of the Turkish downstream oil industry with an emphasis of effect regulatory forces to the pace of financial interactions. The regulatory transformation process has been analysed in terms of its effects on large scale financial transactions, in the form of merges and acquisations. The paper reviews a period of 15 years, during which the Turkish Oil Market has gone through a fundamental regulatory restructuring process from a state governed industry to a regulated market. During this period, oil market law, LPG market law and secondary regulations implemented, an Independent Regulatory Authority established, fuel prices were left to the dynamics of market forces, structural reforms have been implemented and the Competition Authority provided guidance to increase the level of competition. This comprehensive restructuring and liberalisation process was essentially a multidimensional transformation process of the Turkish downstream oil industry. During the initial years of this transformation process, there were strong signs of motion towards a fully liberalised downstream market and the players have responded by several, medium to large scale financial transactions in the form of merges and acquisations. As the winds shift toward a regulated market rather than the full libearisation, the level and the period of these financial transactions have slowed down. However, the overall result of this transformation is strong and sustained growth, improved quality and safety implementations, increased investments and financial transactions. The market practically doubled in financial volume, an average of 6.25% growth in automotive fuels for a period of 15 years has been achieved. The last five-six years of this transformation process however, is marked with interventions from both the Regulatory Authority and the Competition Board, which was responded by the market in the form of substantially reduced investments, lower levels of profits and therefore lower investments in addition to exit decisions of some major international of oil companies. Keywords: Downstream oil industry, Turkish oil market, investments and transactions, growth, regulatory effect, fuels market JEL Classifications: JE31, E61, K2, L11